The Effectiveness of the Jigsaw Teaching Model Assisted by Online Discussion (JAOD) to Improve Learning Outcomes of Capita Selecta Science in Physics Education Students - Abdul Haris Odja (Postgraduate, University of Mataram, 2023)
This study aims to analyze the effectiveness of the JAOD teaching model to improve the learning outcomes of S1 Physics Education S1 students. The research was conducted by applying a one group pre-test and post-test design for 18 students at the State University of Gorontalo, Indonesia. Before and after the learning process was carried out, students were given a pre-test and a post-test test for the science selecta capita learning outcomes. When the learning process is carried out, observations on the practicality of the model are carried out. The data collected from the pre-test and post-test were analyzed using paired t-test and n-gain analysis. The results of the study indicate that the JAOD teaching model is effective in improving the learning outcomes of physics education students' capita selecta of science, which is indicated by: (1) there is a significant difference in the learning outcomes of physics selecta capita learning outcomes before and after the application of cooperative teaching model assisted by online discussion; (2) Improving the learning outcomes of science selecta capita with n-gain in the high category.